Mycorrhizal abundance affects the expression of plant resistance traits and herbivore performance. (25th June 2013) - Vannette, Rachel L.; Hunter, Mark D.; van der, Marcel
Summary The effects of mutualistic interactions on partner phenotype and fitness can vary with many factors, including the abundance of interacting partners. Partner abundance may determine the relative costs and benefits associated with the interaction. Although arbuscular mycorrhizal fungi (AMF) can strongly influence plant phenotype and community interactions, the effects of AMF abundance on plant resistance traits and multitrophic interactions are not well understood. We tested the hypothesis that increasing AMF abundance in soil will increase mycorrhizal colonization and affect plant biomass, foliar phosphorus concentration, the expression of plant resistance and herbivore performance. We inoculated Asclepias syriaca seedlings with Glomus etunicatum, Scutellospora fulgida and a mix of the two species in 11 AMF abundance treatments. We quantified plant phosphorus (P), growth and resistance phenotype and the performance of a specialist herbivore, Danaus plexippus on plants associated with varying amounts of fungi. Increasing abundance of S. fulgida or G. etunicatum in soil increased the proportion of plant root colonized by AMF, but root colonization by a mix of the fungi was not related to inoculum density. The abundance of S. fulgida, but not G. etunicatum, increased per cent foliar P and trichome density, but decreased latex exudation. Abundance of all AMF treatments tended to decrease specific leaf mass (SLM), and the two single‐species treatments unimodally affected the expression of total foliar cardenolides. Increasing abundance of the mix of AMF species also increased above‐ground biomass, foliar P and trichome density, but had little effect on other traits. The presence of AMF, species identity and the AMF abundance all explained significant variation in the expression of plant traits, although their relative contribution varied depending on the trait examined. Mycorrhizal abundance strongly increased caterpillar growth rate, which was associated with a decline in SLM. Synthesis. Variation in mycorrhizal abundance can profoundly influence the expression of plant resistance and subsequent herbivore performance. AMF abundance may be a key, but overlooked factor in determining the outcome of mycorrhizal mutualisms.